2016
DOI: 10.1002/ece3.2243
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choice for a balanced nutrient intake increases the mean and reduces the variance in the reproductive performance of male and female cockroaches

Abstract: Sexual selection may cause dietary requirements for reproduction to diverge across the sexes and promote the evolution of different foraging strategies in males and females. However, our understanding of how the sexes regulate their nutrition and the effects that this has on sex‐specific fitness is limited. We quantified how protein (P) and carbohydrate (C) intakes affect reproductive traits in male (pheromone expression) and female (clutch size and gestation time) cockroaches (Nauphoeta cinerea). We then dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 71 publications
5
52
2
Order By: Relevance
“…Using the GF approach, similar results were found in Nauphoeta cinerea , where females had a low protein requirement for reproduction (Bunning et al., 2016). Interestingly, N. cinerea is also known to have a particularly long lifespan of up to 3 years in the laboratory (Moore & Moore, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the GF approach, similar results were found in Nauphoeta cinerea , where females had a low protein requirement for reproduction (Bunning et al., 2016). Interestingly, N. cinerea is also known to have a particularly long lifespan of up to 3 years in the laboratory (Moore & Moore, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Bunning et al. (2016) suggested that the low protein requirement for reproduction in N. cinerea females was potentially due to their capacity to store excess protein as nitrogen through endosymbiotic interactions. Hence, if females had access to a protein source as juveniles, it might have been possible for them to restore this protein stock when fed on low P:C diet in their adult stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diets chosen to form the four diet pairs were diets 2, 4, 22, and 24 (pair 1: diets 2 and 22; pair 2: diets 2 and 24; pair 3: diets 4 and 22; pair 4: diets 4 and 24), and are the same diets as those used in the choice feeding experiments of Bunning et al. () and Rapkin et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…1). One may, by contrast, also expect the opposite pattern, for example, when low-quality dietary environments represent relatively novel environmental conditions where additional (‘cryptic’) genetic variance is expressed [29], leading to decreased among-individual variance under high-quality dietary conditions (e.g., [14, 30, 31]).…”
Section: Introductionmentioning
confidence: 99%